2004
DOI: 10.1002/adem.200400577
|View full text |Cite
|
Sign up to set email alerts
|

Ceramic Membranes for Filtration Applications — Preparation and Characterization

Abstract: This article gives an overview about the preparation and characterization of asymmetric ceramic membranes that have been developed at our institute within the last years. Depending on the required pore size of the filter active layer for filtration applications ranging from microfiltration (MF) up to nanofiltration (NF) different preparation routes have to be applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 11 publications
(15 reference statements)
0
43
0
Order By: Relevance
“…Alumina membranes based on the application of a template polymer were produced over decades (Benfer et al 2001;Richter et al 1997;Benfer et al 2004) with varying pore sizes and permeation rates. However, there was a current limitation for the practical application of these alumina membranes due to the failure in the production of a complete crack-free layer by the sol-gel technique.…”
Section: Introductionmentioning
confidence: 99%
“…Alumina membranes based on the application of a template polymer were produced over decades (Benfer et al 2001;Richter et al 1997;Benfer et al 2004) with varying pore sizes and permeation rates. However, there was a current limitation for the practical application of these alumina membranes due to the failure in the production of a complete crack-free layer by the sol-gel technique.…”
Section: Introductionmentioning
confidence: 99%
“…The supported membrane could have an even smaller effective pore size due to the capillary forces from the ceramic tube acting on the sol during drying [49]. The polymeric sol-gel route used in this study has demonstrated the ability to produce filtration layers with less than 2 nm pores which have a molecular cut-off < 1,000 Dalton [35]. The water sample use for this study was secondary effluent from one of Melbourne's WWTPs, which contains not only the organic compounds with a molecular weight range of 400-10,000 Daltons as mentioned previously, but also visible particulate contamination.…”
Section: Membrane Filtration Water Treatmentmentioning
confidence: 98%
“…The BET surface area measured in this study for the unsupported TiO 2 membrane is close to the range reported in literature. It is known that the particle size of the starting material has a great impact on the resulting pore size of filtration membranes [35]. Consequently, different preparation routes will result in significant differences in pore size of the filtration layers.…”
Section: N 2 Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pore size of the membrane is controlled by the metal oxide primary particle size, the packing status of the particles, as well as the temperature used to sinter the particles. Ke et al synthesized TiO 2 /ZrO 2 mixed-oxide membranes through a colloidal sol-gel process [44][45][46]. They reported that the mixed-oxide membranes showed a decrease of the average pore size and an increase of the specific surface area compared to the pure oxides.…”
Section: Nanoporous Ceramic Membranesmentioning
confidence: 99%